212k views
5 votes
Solve -7x^2+x+9=-6x quadratic formula

User Phu Ngo
by
5.0k points

1 Answer

2 votes

Answer:


-7x^2+x+9=-6x


-7x^2+x+9+6x=-6x+6x


-7x^2+7x+9=0


quadratic\: formula


x_(1,\:2)=(-7\pm √(7^2-4\left(-7\right)\cdot \:9))/(2\left(-7\right))


\sqrt{-7^(2) -4(-7)*9} =√(301)


x_(1,\:2)=(-7\pm √(301))/(2\left(-7\right))


(-7+√(301))/(2\left(-7\right))


=(-7+√(301))/(-2\cdot \:7)


=(-7+√(301))/(-14)


(-7-√(301))/(2\left(-7\right))


=(-7-√(301))/(-2\cdot \:7)


=(-7-√(301))/(-14)


answer=(7+√(301))/(14)


OAmalOHopeO